Concurrent KRAS p.G12C mutation and ANK3::RET fusion in a patient with metastatic colorectal cancer: a case report - Tillmann Bedau; Carina Heydt; Udo Siebolts; Thomas Zander; Max Kraemer; Heike Loeser; Reinhard Buettner; Alexander Quaas (BMC, 2024)
Abstract Background Colorectal cancer (CRC) frequently involves mutations in the KRAS gene, impacting therapeutic strategies and prognosis. The occurrence of KRAS mutations typically precludes the presence of RET fusions, with current medical literature suggesting a mutual exclusivity between these two genetic alterations. We present a unique case that challenges this notion. Case Presentation An 85-year-old female with metastatic CRC was found to have a combination of genetic anomalies that is to the best of our knowledge not yet described in the medical literature: a KRAS p.G12C mutation, associated with oncogenesis and treatment resistance, and an ANK3::RET fusion, an infrequent but targetable mutation in CRC. This molecular profile was uncovered through comprehensive genomic sequencing after the patient experienced metachronous tumor dissemination. The presence of both genetic events complicates the treatment approach. Conclusions The identification of both a KRAS p.G12C mutation and an ANK3::RET fusion in the same CRC patient adds a new layer to the oncogenic landscape and treatment considerations for CRC. It highlights the intricate decision-making required in the era of precision medicine, where targeted therapies must be carefully chosen and potentially combined to combat complex genetic profiles. The case emphasizes the urgency of investigating the clinical effects of concurrent or sequential use of KRAS p.G12C and RET inhibitors to inform future therapeutic guidelines and improve patient outcomes in similar cases.